Race and contrast-induced nephropathy in patients undergoing coronary angiography and cardiac catheterization. (1st March 2017) - Chawla, Raveen; Turlington, Jeremy; Arora, Pradeep; Jovin, Ion S
Abstract: Contrast-induced nephropathy (CIN) is an acute worsening of renal function after receiving intravascular contrast during a procedure. Some of the predisposing factors include underlying diabetes, chronic kidney disease, congestive heart failure, periprocedural hypotension, anemia, contrast volume, and osmolality of contrast; however, it remains unclear if risk varies for CIN with race and ethnicity. There is evidence in the literature showing the link between race/ethnicity and the discrepancies in the utilization of preventive care services and the resources related to cardiovascular and renal health. While these disparities continue to exist and affect some of the predictors of CIN, this review will explore the extent to which race and ethnicity directly affect CIN. Highlights: Racial and ethnic disparities continue to exist in regards to cardiovascular and renal health resources utilization. CIN is an acute worsening of renal function after receiving intravascular contrast during a procedure. Risk factors of CIN such as hypertension, chronic kidney disease, etc. are affected by racial/ethnic disparities. Further investigation is warranted on how these racial/ethnic disparities affect CIN.